Vasodilation Mechanism of Cerebral Microvessels Induced by Neural Activation under High Baseline Cerebral Blood Flow Level Results from Hypercapnia in Awake Mice. (November 2015) - Nishino, Asuka; Takuwa, Hiroyuki; Urushihata, Takuya; Ito, Hiroshi; Ikoma, Yoko; Matsuura, Tetsuya
Abstract: Objective: We investigated the effects of the baseline CBF level at resting state on neurovascular coupling. Methods: Diameters of arterioles, capillaries, and venulas in awake mouse brain were measured by a two‐photon microscope. Vasodilation in each of the cerebral vessels was caused by three experimental conditions: (1) sensory stimulation, (2) 5% CO2 inhalation (hypercapnia), (3) simultaneous exposure to sensory stimulation and 5% CO2 inhalation. CBF and CBV were also measured by a microscope and a CCD camera. Results: Increases in CBF and CBV were observed under all experimental conditions. After the increases in CBF and CBV due to hypercapnia, additional increases in CBF and CBV occurred during sensory stimulation. Diameter changes in arterioles were significantly larger than those in capillaries and venulas under both sensory stimulation and 5% CO2 inhalation. Additional vasodilation from sensory stimulation was observed under hypercapnia. The diameter change in each vessel type during sensory stimulation was maintained under simultaneous exposure to sensory stimulation and hypercapnia. Conclusions: The diameter change of cerebral vessels during neural activation is reproducible regardless of whether baseline CBF has increased or not. Our finding directly demonstrates the concept of uncoupling between energy consumption and energy supply during cortical activation.